Post-liberal regionalism in South America: in a depoliticization phase? The cases of ALBA, UNASUR and MERCOSUR - Alvarez, María Victoria (2019)
After five decades of waves of boom and decline of regionalism, in the early years of the 21st century, South American regionalism was reconsidered in a post-liberal design. In particular, an initiative of complementarity and cooperation materialized in ALBA, and a scheme of cross-sectoral dialogue and political cooperation, UNASUR. Meanwhile, MERCOSUR, a resilient regionalist scheme, was also renovated in post-liberal terms. A decade after the rise of post-liberal regionalism, we attend to a phase of less dynamism. In this paper we describe the latest developments of ALBA and UNASUR, as well as MERCOSUR, following the perspective of Dabène of cycles of politicization. The question is whether these schemes are in a phase of depoliticization. If this is so, this development raises the question of whether they will be the sufficiently resilient as to overcome this phase and move toward one of deeply repoliticization.